Palliative Care Evidence Review Service (PaCERS): a knowledge transfer partnership - Mala Mann; Amanda Woodward; Annmarie Nelson; Anthony Byrne (BMC, 2019)
Abstract The importance of linking evidence into practice and policy is recognised as a key pillar of a prudent approach to healthcare; it is of importance to healthcare professionals and decision-makers across the world in every speciality. However, rapid access to evidence to support service redesign, or to change practice at pace, is challenging. This is particularly so in smaller specialties such as Palliative Care, where pressured multidisciplinary clinicians lack time and skill sets to locate and appraise the literature relevant to a particular area. Therefore, we have initiated the Palliative Care Evidence Review Service (PaCERS), a knowledge transfer partnership through which we have developed a clear methodology to conduct evidence reviews to support professionals and other decision-makers working in palliative care. PaCERS methodology utilises modified systematic review methods as there is no agreed definition or an accepted methodology for conducting rapid reviews. This paper describes the stages involved based on our iterative recent experiences and engagement with stakeholders, who are the potential beneficiaries of the research. Uniquely, we emphasise the process and opportunities of engagement with the clinical workforce and policy-makers throughout the review, from developing and refining the review question at the start through to the importance of demonstrating impact. We are faced with the challenge of the trade-off between the timely transfer of evidence against the risk of impacting on rigour. To address this issue, we try to ensure transparency throughout the review process. Our methodology aligns with key principles of knowledge synthesis in defining a process that is transparent, robust and improving the efficiency and timeliness of the review. Our reviews are clinically or policy driven and, although we use modified systematic review methods, one of the key differences between published review processes and our review process is in our relationship with the requester. This streamlining approach to synthesising evidence in a timely manner helps to inform decisions faced by clinicians and decision-makers in healthcare settings, supporting, at pace, knowledge transfer and mobilisation.